2015
DOI: 10.1016/j.srhc.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Which role do midwives and gynecologists have in smoking cessation in pregnant women? – A study in Flanders, Belgium

Abstract: These findings suggest that training in communication skills and dealing with resistance should be offered, i.e. by using motivational interviewing. It could be considered that a trained midwife or tobaccologist is part of an obstetrical team or that the AAR-method (Ask-Advise-Refer) is used instead of the 5 A's framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 17 publications
3
26
0
4
Order By: Relevance
“…Physician group was also associated with performance, with Obstetricians performing the AAR better, and the 5A's less well, compared to NFATSIH GPs. These findings are consistent with similar studies from other countries, with health providers providing Ask and Advise components more than with the other components of SCC [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . The barriers reported in this study are very similar to those cited in a non-systematic review 9 : lack of time; low confidence in personal skills; and a perception that smoking cessation interventions are not effective 9,26 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Physician group was also associated with performance, with Obstetricians performing the AAR better, and the 5A's less well, compared to NFATSIH GPs. These findings are consistent with similar studies from other countries, with health providers providing Ask and Advise components more than with the other components of SCC [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . The barriers reported in this study are very similar to those cited in a non-systematic review 9 : lack of time; low confidence in personal skills; and a perception that smoking cessation interventions are not effective 9,26 .…”
Section: Discussionsupporting
confidence: 90%
“…A limitation of this work is the low response rate, indicating this sample may not be generalizable to all Australian GPs and Obstetricians. In spite of this, these findings are consistent with other surveys globally [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] , supporting the cautious assumption that this is a true or over-estimation of actual practices. The low response rate needs to be kept in mind when interpreting these findings, and these results need to be confirmed by a larger more representative sample.…”
Section: Limitations and Strengthssupporting
confidence: 89%
See 1 more Smart Citation
“…This study is part of a larger survey with an observational, longitudinal design, aiming to provide insight into the determinants of smoking and smoking cessation among Flemish pregnant women [10,17].…”
Section: Methodsmentioning
confidence: 99%
“…Factors influencing the provision of smoking cessation counselling based on the 5As model include time constraints [115,116], and inadequate knowledge of cessation interventions and training to implement a brief counselling intervention during pregnancy [116,117]. In line with this, surveys of midwives and gynecologists found that their knowledge of NRT use in pregnancy, was insufficient and thus not recommended to pregnant women [118,119]. “Ask”, “Advise” and to a lesser extent, “Assist” of the 5A’s model, were implemented in smoking cessation communication between these healthcare providers and their clients, but there were important barriers to providing counselling which included lack of time, lack of communication skills in sensitive topics such as smoking cessation and dealing with resistance.…”
Section: Determinants Of Healthmentioning
confidence: 99%